Ways of optimization of lead-polluted black earth soils in the soil-plant system - Yana Biletska; Alla Nekos; Anastasia Bekhter; Anna Krivtsova; Olga Brayninger (Вісник Харківського національного університету імені В.Н. Каразіна. Серія Геологія. Географія. Екологія, 2021)
the most urgent problems of today. Ensuring the environmental safety of food raw materials and food products is one of the main tasks that determine the health of the human population and the preservation of its gene pool.